The Effect of Operating Cash Flow, Investment Cash Flow, and Financing Cash Flow on Stock Returns in Manufacturing Companies Listed on the Indonesian Stock Exchange: (Case Study: Companies that Produce Concrete) - Deris Lazuardi; Rokhmat Subagiyo; Muhammad Aswad (Yayasan Inovasi Kemajuan Intelektual, 2023)
Stock returns serve as a measure for investors to evaluate a company’s investment potential and also illustrate the company’s success. This study aims to analyze how operating cash flow, investment cash flow, and financing cash flow affect stock returns in manufacturing companies listed on the Indonesia Stock Exchange, which produce concrete. This study uses a quantitative approach utilizing secondary data. The data used comes from company financial reports and Investing.com sources, and to process the data, the author uses EViews version 13 Enterprise software. The period used in this study is five years, from 2020 to 2024. The method used is panel data regression analysis with the Common Effect Model (CEM) approach. The CEM model was chosen because the model selection test results showed that this model was the best for this study. The study's results indicate that the variables of operating cash flow, investment cash flow, and financing cash flow have no effect and are not significant on the stock returns of manufacturing companies listed on the Indonesia Stock Exchange that produce concrete, either partially or simultaneously. The Adjusted R-squared (Adj. R2) value of 40% indicates that the variables used can only explain 40% of the changes in stock returns, while factors outside the variables in the model influence the other 60%. The R-squared (R2) value of 52%, which according to Chin (1998) is in the moderate category, means that these variables are sufficient to explain changes in stock returns.